The Effect of Teaching Summarization Strategies on Reading Comprehension of Science and Humanities Iranian High school Students - Azam Sadat Pourhosseini Maybodi; Ashraf Haji Maibodi (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2017)
This study investigated the effect of teaching summarization strategies on the reading comprehension of English as Foreign Language (EFL) high school students. To this end, 80 high-school students from science and humanities sections were divided to two groups of 40 each. Two reading comprehension tests were developed and administered as pre-test and post-test. The obtained data that was analyzed using SPSS software showed that EFL learners in both groups showed significantly more improvement in their reading comprehension from the pre-test to the post-test. However, the numerical findings obtained from the paired samples t-test showed that students in the science group outperformed those who were in the humanity group and their scores seemed to be more statistically significant. The major pedagogical implication of this study is that summarization strategy can help to improve the reading comprehension of EFL high school students in Iran.